Ion charge separation with new generation of nuclear emulsion films - Montesi M.C. (Open Physics, 2019)
In hadron therapy, the accelerated ions, interacting with the body of the patient, cause the fragmentation of both projectile and target nuclei. The fragments interact with the human tissues depositing energy both in the entrance channel and in the volume surrounding the tumor. The knowledge of the fragments features is crucial to determine the energy amount deposited in the human body, and - hence - the damage to the organs and to the tissues around the tumor target.